Decay of a Transmission Problem with Memory and Time-varying Delay (Journal of Partial Differential Equations, 2016)
In this article we consider a transmission problem with memory in a bounded domain and varying delay term in the first equation. Under suitable assumptions on the weight of the damping and the weight of the delay, we show the exponential stability of the solution by introducing a suitable Lyaponov functional.
Keywords: Wave equation; transmission problem; varying delay term; memory; exponential stability